RISK FACTORS FOR PREGNANCY-INDUCED HYPERTENSION - Januzović, Vladislava (PONS - medicinski časopis, 2015)
ABSTRACT The aim of the research’s work is to fortify two groups of patients- women with hypertensive pregnancy induced and women with orderly pregnancy- if they are different in some tested factors of the risk, concerning their identification. Material and methods: investigation for need work has been carried out in health centre „Sid“ in Sid, in the Dispensary for women. In the aim of taking necessary information for research a poll’s list has been used independently formed. The pattern of the investigation consist of 200 pregnant women divides in two groups. The first group were a 100 pregnant women with hypertension. The second group were a 100 pregnant women with orderly pregnancy. The pregnant women from two groups were selected with the method of random choice. Results: Researching the relative factors of risk for appearance hypertension in pregnancy induced , the results were next: 34% pregnant women had hypertension induced between 26- 30 years old. The ordinary age of pregnancy with disturbance was 29,7 gestational weeks. In the group of pregnant women with hypertension induced at 37 % BMI is between 25 and 29,99 and at 38% over 30. 35% pregnant women with hypertension induced eat salted and spiced food, and 42% of pregnant women eat only sometimes salted and spiced food. Conclusion: There aren’t so important differences in living period between pregnant women with hypertension induced and women with orderly pregnancy. The average age of pregnant women with hypertensive induced is 25,7 years old. Hypertensive induced in pregnant women appears in the first pregnancy, at pregnant women with increased values BMI at pregnant women with reduced activity, at pregnant women who smoke and pregnant women who eat salted and spiced food. Key words: risk factors; pregnancy; pregnancy-induced hypertension; hypertension